A comparison of the inhibitory activities of Lactobacillus and Bifidobacterium against Penicillium expansum and an analysis of potential antifungal metabolites. Issue 18 (26th August 2020) - Qiao, Nanzhen; Yu, Leilei; Zhang, Chengcheng; Wei, Chaozhi; Zhao, Jianxin; Zhang, Hao; Tian, Fengwei; Zhai, Qixiao; Chen, Wei
ABSTRACT: The infection of fruits by Penicillium expansum ( P. expansum ) do not only cause economic loss but also potentially endanger human health, especially because few biocontrol agents against this fungus have been well studied yet. In this work, to verity the antifungal activity against P. expansum of 22 Bifidobacterium and 44 Lactobacillus, dual-culture overlay assay, microtiter plate well assay and agar spot assay were successively performed. One of the strain, Bifidobacterium adolescentis ( B. adolescentis ) CCFM1108 exhibited the most potent inhibition ability among all tested strains. Additionally, we showed that multiple antifungal compounds produced by tested strain synergistically inhibit the growth of P. expansum, including lactic acid, acetic acid, 3-phenyllactic acid and p -hydroxyphenyllactic acid. Those active compounds mentioned were detected in the cell-free supernatant and characterized by metabolomics analysis using GC-MS. Correspondingly, B. adolescentis CCFM1108 supernatant disrupted plasma membrane integrity of the P. expansum mycelial and drastically reduced patulin production in P. expansum . The inhibitive effects of B. adolescentis CCFM1108 were also confirmed with three other P. expansum strains. The active inhibitory properties of Bifidobacterium strains, especially B. adolescentis CCFM1108, indicate that B. adolescentis can be potentially used as a novel bioagent to prevent or delay fungal spoilage on fruit. Abstract : The highly effective antifungal properties of Bifidobacterium strains against Penicillium expansum .